Parastomal Hernia Repair and Reinforcement: The Role of Biologic and Synthetic Materials - Gillern, Suzanne; Bleier, Joshua I. S. (Clinics in Colon and Rectal Surgery, 2014)
Parastomal hernia is a prevalent problem and treatment can pose difficulties due to significant rates of recurrence and morbidities of the repair. The current standard of care is to perform parastomal hernia repair with mesh whenever possible. There exist multiple options for mesh reinforcement (biologic and synthetic) as well as surgical techniques, to include type of repair (keyhole and Sugarbaker) and position of mesh placement (onlay, sublay, or intraperitoneal). The sublay and intraperitoneal positions have been shown to be superior with a lower incidence of recurrence. This procedure may be performed open or laparoscopically, both having similar recurrence and morbidity results. Prophylactic mesh placement at the time of stoma formation has been shown to significantly decrease the rates of parastomal hernia formation.
Keywords: parastomal hernia; biologic mesh; synthetic mesh; Sugarbaker technique; keyhole technique